Mixed-trophies biofilm cultivation in capillary reactors - Heuschkel, Ingeborg (MethodsX, 2019)
The biocatalytic application of photoautotrophic organisms is a promising alternative for the production of biofuels and value-added compounds as they do not rely on carbohydrates as a source of carbon, electrons, and energy. Although the photoautotrophic organisms hold potential for the development of sustainable processes, suitable reactor concepts that allow high cell density (HCD) cultivation of photoautotrophic microorganisms are limited. Such reactors need a high surface to volume ratio to enhance light availability. Furthermore, the accumulation of high oxygen concentrations as a consequence of oxygenic photosynthesis, and its inhibitory effect on cell growth needs to be prevented. Here, we present a method for HCD cultivation of oxygenic phototrophs based on the co-cultivation of different trophies in a biofilm format to avoid high oxygen partial-pressure and attain HCDs of up to 51.8 g(BDW) L(−1) on a lab scale. In this article, we show: • A robust method for mixed trophies biofilm cultivation in capillary reactors; • Set-up and operation of a biofilm capillary reactor; • A method to quantify oxygen in the continuous biofilm capillary reactor.